Molecularly imprinted cyclodextrin nanosponges for the controlled delivery of L-DOPA: perspectives for the treatment of Parkinson's disease. (1st December 2016) - Trotta, Francesco; Caldera, Fabrizio; Cavalli, Roberta; Soster, Marco; Riedo, Chiara; Biasizzo, Miriam; Uccello Barretta, Gloria; Balzano, Federica; Brunella, Valentina
ABSTRACT: Background : L-DOPA is an amino acid precursor to the neurotransmitter dopamine that is extensively used as a prodrug for the treatment of Parkinson's disease. However, L-DOPA is an unstable compound: when exposed to light or added to aqueous solutions, it may degrade, compromising its therapeutic properties. Methods : In this work, a new type of drug-loaded cyclodextrin-based nanosponge, obtained using molecular imprinting, is described for the prolonged and controlled release of L-DOPA. The molecularly imprinted nanosponges (MIP-NSs) were synthesized by cross-linking β-cyclodextrin with 1, 1ʹ-carbonyldiimidazole in DMF in the presence of L-DOPA as a template molecule. TGA, DSC and FTIR analyses were performed to characterize the interactions between L-DOPA and the two nanosponge structures. Quantitative NMR spectroscopy was used to determine the amount and the affinity of L-DOPA entrapped in the nanosponges. The in vitro L-DOPA release kinetics from the NSs were quantitatively determined by HPLC analysis. Results : The MIP-NSs show a slower and more prolonged release profile than the non-imprinted nanosponges. No degradation of the L-DOPA hosted in the MIP-NSs was observed after long-term storage at room temperature. Conclusions : The MIP-NSs are a promising alternative for the storage and controlled delivery of L-DOPA.